Economic policy uncertainty and stock market participation - Enikő Gábor-Tóth; Dimitris Georgarakos (Goethe University Frankfurt, Center for Financial Studies (CFS), 2018)
Does economic policy uncertainty affect household stockholding? To answer this question we create a novel measure of household exposure to economic policy uncertainty news by combining survey information on the hours a household spends in reading newspapers and the frequency of such news in the popular press during a household's pre-interview period. After controlling for household fixed effects, month-year fixed effects and time-varying cognitive skills, we find that households with a higher exposure to economic policy uncertainty news are less likely to invest in stocks held directly or through mutual funds. This effect is independent from the market volatility index and household (first-moment) expectations about the stock market index.
urn:nbn:de:hebis:30:3-437410
Keywords: D14; D81; G11; 330; economic policy uncertainty; household finance; stockholding; text analysis